Edukasi Kesiapsiagaan Gempa Bumi bagi Siswa Sekolah Dasar di Depok, Jawa Barat - Salwa Febriana Ekasari Siregar; Suparni Suparni; Seftiani Syafira; Maritza Adelia Putri; Canttika Canttika; Nadya Nur Syafina Putri; Agung Raharjo (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2025)
Indonesia, located within the Pacific Ring of Fire, is highly susceptible to natural disasters, particularly earthquakes. These events pose significant risks, including infrastructure damage, injuries, and psychosocial effects, especially among populations lacking proper preparedness, such as elementary school children. This community service activity focuses on increasing earthquake preparedness awareness among 3rd-grade students at Lazuardi Depok, West Java. The goal was to educate and enhance students' understanding of earthquake safety measures through interactive and engaging activities. The approach included presentations, simulations, and educational videos. The methods used involved pre-tests and post-tests to assess students' knowledge before and after the session. Results indicated an improvement in earthquake preparedness, with post-test scores increasing by 4.8 points compared to the pre-test. Additionally, the students demonstrated their ability to perform appropriate safety actions during earthquake simulations. This program effectively contributed to raising awareness and enhancing earthquake preparedness among students. It is recommended that similar educational initiatives be conducted regularly to ensure the long-term retention of preparedness skills.